(untitled) (Research, Society and Development, 2021)
The macauba (acrocomia aculeata) is a PANC species native to Brazil, its fruits have an edible mesocarp with a yellowish or whitish color and a fibrous and mucilaginous consistency. This study aimed to analyze the nutritional constituents of the mesocarp of acrocomia aculeata. This is an experimental study with a quantitative approach, where the macauba pulp was used for the analysis of the centesimal composition (humidity, ashes, proteins, lipids, fibers and carbohydrates), performed in triplicates in the laboratory of food quality control in Teresina-PI. With the results obtained, it is observed that the sample analyzed has a high content of moisture (57.6%), fiber (13.5%) and total carbohydrates (21.22%), indicating that the use of macauba pulp can be an excellent food option, a source of energy and total fiber, contributing to the promotion of health. In conclusion, the pulp of acrocomia aculeata can be considered as a source of high total dietary fiber, and can be used as a dietary supplementation helping to achieve the daily recommendation of fiber in the diet and as an alternative or complementary treatment of various diseases, indicating its potential for the development of products with functional claims.